The efficacy of rooibos Aspalathus linearis as an ergogenic aid during exercise. (3rd May 2019) - Davies, Simeon E.H.; Marnewick, Jeanine L.; West, Sacha; Taliep, Mogammad Sharhidd; Rautenbach, Fanie; Gamieldien, Raeeq
This study investigated whether rooibos herbal tea Aspalathus linearis has an ergogenic effect during a fatiguing arm strength test to exhaustion. Thirty-two male participants were randomised in a single blinded, cross-over placebo controlled study in which they ingested standardised rooibos or placebo capsules for four weeks prior to a fatiguing elbow flexion/extension exercise test entailing five sets/bouts of 15 repetitions of maximum voluntary contractions separated by 10-second rest intervals on a Biodex System 3 at a speed of 60° per second. Peak torque flexion (Nm) was consistently higher in the rooibos experimental (Re) compared to the placebo control (Pc) across the five exercise bouts, and this performance trend during flexion was also seen in the total work (joules) completed, although not significant (P > 0.05). It appears that the antioxidant properties of rooibos, may have contributed to an improvement in physical performance during a maximal isokinetic arm exercise protocol to induce fatigue.